PostgreSQL up and running - Obe, Regina O.; Hsu, Leo S. (O'Reilly Media, 2015)
Thinking of migrating to PostgreSQL? This clear, fast-paced introduction helps you understand and use this open source database system. Not only will you learn about the enterprise class features in versions 9.5 to 10, you'll also discover that PostgeSQL is more than a database system-it's an impressive application platform as well.